551 The Impact of Technology on Improving the Learning Process in Physical Education Lessons for Medically-Exempt Pupils (Balneo and PRM Research Journal, 2024)
Background and Study Aim. The focus of our attention lies on the medically exempt students, who more often than not take part in physical education (P.E.) classes as spectators, without any tasks to complete in accord with the collective work of their classmates or the objective of the lesson. The purpose of the present research is to develop and implement the application Info-Scutit-Sport in the P.E. lesson to the purpose of teaching and assessing medically-exempt students, who are present, but do not take part in the lesson. Material and Methods. The present paper emphasises the usefulness of the Info-Scutit-Efort [Info-Exempt-Effort] application aimed at the active and mindful inclusion of 55 students (aged=11.29±1.84), who have a medical exemption (58.2% total and 42.8% partial) in the P.E. lesson. The application, in an improved form, comprises the entire content of the curriculum of physical education in secondary school, transformed into 2080 questions with three answer variants, with 1500 processed images, that may be accessed with the teacher’s accord, on the student’s own phone. The assessment obtained by means of the application after the working session may provide the student with a mark for the information taught before, if he accesses topics from the previous lessons, or a mark for the current assessment in order to test the active and mindful participation in the lesson which is being taught. Conclusions. The study utilized multiple statistical tests to establish a relationship between platform access time and student performance. The results of the tests demonstrated that platform use time has a significant impact on student performance, with longer platform access time leading to higher marks. The study concluded that the proposed model is significant, as it identifies platform access time as a crucial factor in determining student performance. Moreover, the study found that even small increases in platform access time can lead to significant improvements in student performance, with an increase of one unit resulting in a 0.54% increase in marks.